The effectiveness of PMRI Approach Aided by Educational Props to Improve Student’s Mathematical Literacy - SETYANINGSIH, HESTI; Wardono, Wardono; Prabowo, Ardhi (Unnes Journal of Mathematics Education, 2017)
Penelitian ini bertujuan mengetahui keefektifan pembelajaran dengan model PMRI berbantuan alat peraga untuk meningkatkan kemampuan literasi matematika siswa. Populasi dalam penelitian ini adalah siswa kelas VIII SMP Negeri 1 Simo Boyolali tahun pelajaran 2015/2016. Metode yang digunakan dalam penelitian ini adalah mixed method dan pemilihan sampel dengan cara random sampling. Data diperoleh dengan metode tes untuk menentukan hasil belajar siswa yang kemudian dianalisis dengan uji proporsi; uji kesamaan dua rata-rata, dan uji peningkatan Gain ternormalisasi Hasil penelitian adalah (1) kelas eksperimen mencapai ketuntasan belajar klasikal 75%, (2) kemampuan literasi matematika siswa kelas eksperimen lebih dari kemampuan literasi matematika siswa kelas kontrol, (3) penerapan pembelajaran dengan pendekatan PMRI berbantuan alat peraga pada materi bangun ruang sisi datar dapat meningkatkan kemampuan literasi matematis siswa. This study aims to determine the effectiveness of teaching methods assisted PMRI props to improve students' mathematical literacy. The population of this study were students of class VIII SMP Negeri 1 Simo Boyolali academic year 2015/2016. The method used in this research is mixed method and selection of samples by means of random sampling. Capturing the subjects in this study using purposive sampling, the subject is taken as 6 students. Data obtained with a test method for determining the learning outcomes of the students then analyzed by proportion of test, equality test two averages, and test an increase in Gain normalized. The results are (1) the experimental class achieve mastery learning classical 75%, (2) the mathematical literacy of student in experiment class over the mathematical literacy of students in control class, (3) the application of learning PMRI assisted by props on material geometry flat side can improve students' mathematical literacy.